2013
DOI: 10.7314/apjcp.2013.14.2.825
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Five-Year Survival of Cervical Cancer Patients Treated in Hospital Universiti Sains Malaysia

Abstract: The five-year survival of cervical cancer patients in this study was low. The survival of those diagnosed at an advanced stage was low compared to early stages. In addition, those who underwent surgery had higher survival than those who had no surgery for primary treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
3
16
1
Order By: Relevance
“…In contrast with the high survival rate in this study, which is 71.1%, a recent local study done by Razak et al, (2013) reported the overall 5-year survival rate of cervical cancer was only 39.7%. The contrary finding was due to the small sample size and characteristic.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In contrast with the high survival rate in this study, which is 71.1%, a recent local study done by Razak et al, (2013) reported the overall 5-year survival rate of cervical cancer was only 39.7%. The contrary finding was due to the small sample size and characteristic.…”
Section: Discussioncontrasting
confidence: 94%
“…Conversely, poor survival and low quality of life occur when the cancer is detected at later stages of the disease. The chances of survival for patients diagnosed with stage IA is nearly 100% compared to patients diagnosed with stage IVB who has chances of survival of only 20% (Kyrgiou and Shafi, 2010;Razak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In studies that were conducted in Asia, the overall five-year survival rate was 18% in Malaysia (Razak et al, 2010), 30.5 % in India (Yeole et al, 2003), 52.8% in Korea (Choi et al, 2014), and 61% in Taiwan (Liu et al, 2010). Due to limited access to diagnostic and treatment services in low-income communities and to the high cost of services, people present with advanced stage lip and oral cavity cancer at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the most common cancers in developing countries, and it also represents a major health issue in Korea and Japan, economically developed Asian nations (Konno et al, 2008;Razak et al, 2013). In Korea, cervical cancer accounted for 9.8% of new cancer cases in 2002, although the age-standardized incidence has steadily declined from 19 per 100,000 women in 1993-1995 to 15 per 100,000 women in 1999-2002(Chung et al, 2006Shin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%